Fiscal geographies: "Placing" taxation in urban geography. Issue 4 (21st April 2019) - Tapp, Renee; Kay, Kelly
ABSTRACT: As the state's primary means of both redistributing wealth and incentivizing private investment, tax plays an outsized role in a range of critical urban processes, including (re)development, gentrification, financialization, and local and regional governance. We argue, through reference to existing literature in urban and economic geography, as well as our own research on taxation and the state, that urban scholarship could benefit by close and careful engagement with taxation and the tax system. We term this new vein of research "fiscal geographies" and see it as offering potential for more nuanced study of urban political economy, politics, and processes.